Mobile application-based media learning and its’ effect on students’ learning motivation - Fajar Indra Kusuma; Nunuk Suryani; Sri Sumaryati (Institute of Advanced Engineering and Science, 2022)
Online learning is a solution used during the COVID 19 pandemic. This study aimed to determine the conditions of learning during the pandemic and the development of mobile application-based learning media. This was a research and development (R&D) in the context of developing mobile application-based learning media. The results of the development of learning media by researchers indicate that experts and students have positive opinions about this cellular application-based learning media. All experts from media experts, materials experts and expert practitioners stated that this media is